Fundamentos da circulação de saberes nos espaços religiosos de matriz africana: análise no Ilê Alaketu Asè Omô Logunédè - Santos, Ademir Barros (2018)
From a pedagogical and anthropological perspective, this research sought to identify the foundations present in the circulation, diffusion, apprehension and perpetuation of knowledge in environments linked to the religious matrix of African origin, understanding, as circulation, the transference and apprehension of the ritual knowledge and practices inherent in that belief system. The theme of study is the Ketu nation candomblé, particularly the Ilê Alaketu Asè Omô Logunédè Cult House, in which complex rituals continue to be learned and apprehended, perpetuated and transmitted, notwithstanding the absence of the traditional figure of the master or a written culture, as well as continually facing the harsh repudiation of Western Judeo-Christian societies, exacerbated along the historical slave trade process. The methodology used was qualitative and included bibliographical analysis, data collection in the field and participant observation. Theoretically, it relied on renowned names such as Kabengele Munanga, Amadou Hampâté Bâ, Roger Bastide and Pierre Verger, as well as on research related to the subject, such as “Educação nos Terreiros" (not avaiable in English), developed by Stella Guedes Caputo and "Convivendo com os Orixás" (not published) by Karla Geyb da Silva Queiroz; also in speeches such as that of Maria Stella de Azevedo Santos, Mother Stella de Oxossi, delivered in 2013, when she took office at the Bahia Academy of Letters, as well as a survey of the formation and history of candomblé in Brazil. Among the results achieved, it was observed that the adherence between the African cultural values and the practices of knowledge transmission in the diaspora happens in a very effective way, characterized by the respect to the longevity, communal dependency, circularity, playfulness, notion of a necessary complementarity among all the individuals, as well as other elements that are part of the processes studied. Thus, this dissertation aims to collaborate with the production of knowledge in the field of fundamentals of educational processes of non-school education.